Training in Effective use of Vision in Students with Low Vision - Dhanalakshmi, K. (Voices of Teachers and Teacher Educators, 2020)
Vision is the primary sensory input. About 80% of learning takes place through the visual system (State-wide Vision Resource Centre). Vision is responsible for seeing the world and is also the unifying sense allowing sighted people to integrate their sensory experiences. At three months of age vision is the lead sensory modality and at six months it is the primary source of information about the environment. A huge number of children with visual impairment have some degree of residual vision. The amount of residual vision varies greatly among individuals. It is very important to encourage the person with low vision to use his/her residual vision at maximum level. Functional Vision refers to the way in which the person uses whatever vision he or she has. Systematic training will enhance the functional vision of individuals with low vision.